Faktor-faktor Yang Mempengaruhi Profitabilitas Bank Umum Syariah di Indonesia - Hanum Yuniastika (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2018)
One of the indicators of the financial performance of a banking was the level of profitability. Each organization is geared towards maintaining its financial performance, by running their business efficiently. The higher profitability of a bank, could be seen on financial performance. The size of financial performance is measured by several variables: return on asset (ROA), current asset ratio (CAR), non performing financing (NPF), financial debt ratio (FDR), biaya operasional pokok organisasi (BOPO) and firms size (Size). This research is a quantitative study, the type of data used is secondary data obtained from Bank Indonesia, the type of data used time series data that is financial data of Sharia General bank year 2012-2016 from 5 sharia banks In Indonesia. The data analysis tools used are multiple regression analyses with SPSS 17.0. Data analysis results confirm that ROA, CAR, NPF, FDR, BOPO, and Size generally influence the profitability of Sharia general Bank in Indonesia. A partial CAR dan FDR does not have any effect on ROA, while NPF, BOPO and size have been affected by ROA.